Skp2 inhibits osteogenesis by promoting ubiquitin–proteasome degradation of Runx2 - Thacker, Gatha; Kumar, Yogesh; Khan, Mohd. Parvez; Shukla, Nidhi; Kapoor, Isha; Kanaujiya, Jitendra Kumar; Lochab, Savita; Ahmed, Shakil; Sanyal, Sabyasachi; Chattopadhyay, Naibedya; Trivedi, Arun Kumar (Biochimica et biophysica acta, 2016)
Osteogenic transcription factor Runx2 is essential for osteoblast differentiation. The activity of Runx2 is tightly regulated at transcriptional as well as post-translational level. However, regulation of Runx2 stability by ubiquitin mediated proteasomal degradation by E3 ubiquitin ligases is little-known. Here, for the first time we demonstrate that Skp2, an SCF family E3 ubiquitin ligase negatively targets Runx2 by promoting its polyubiquitination and proteasome dependent degradation. Co-immunoprecipitation studies revealed that Skp2 physically interacts with Runx2 both in a heterologous as well as physiologically relevant system. Functional consequences of Runx2–Skp2 physical interaction were then assessed by promoter reporter assay. We show that Skp2-mediated downregulation of Runx2 led to reduced Runx2 transactivation and osteoblast differentiation. On the contrary, inhibition of Skp2 restored Runx2 levels and promoted osteoblast differentiation. We further show that Skp2 and Runx2 proteins are co-expressed and show inverse relation in vivo such as in lactating, ovariectomized and estrogen-treated ovariectomized animals. Together, these data demonstrate that Skp2 targets Runx2 for ubiquitin mediated degradation and hence negatively regulate osteogenesis. Therefore, the present study provides a plausible therapeutic target for osteoporosis or cleidocranial dysplasia caused by the heterozygous mutation of Runx2 gene. •E3 ubiquitin ligase Skp2 physically interacts with Runx2.•Skp2 promotes ubiquitin-mediated proteasome dependent degradation of Runx2 and negatively affects functions.•Inhibition of Skp2 restores Runx2 levels and promotes osteoblast differentiation.•Skp2 and Runx2 proteins are co-expressed and show an inverse relation in vivo during osteoblast differentiation.